Numerical Analysis of Outlet Number Effects on Temperature Distribution in a Briquette Oven Using CFD - Alviani Hesthi Permata Ningtyas; Siti Duratun Rosady; Muhammad Wildanus Sholih (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
The performance of briquette drying systems is strongly influenced by airflow distribution and thermal uniformity within the drying chamber, which are governed by outlet configuration and internal flow patterns. However, limited studies have systematically quantified the effect of exhaust outlet arrangements on the coupled heat transfer and fluid flow behavior in industrial-scale briquette ovens. This study aims to numerically investigate the influence of single-, double-, and four-outlet configurations on airflow characteristics, temperature distribution, and overall thermal performance of a briquette drying oven. A three-dimensional geometric model representing the combustion chamber, drying chamber, and briquette racks was developed and analyzed using Computational Fluid Dynamics (CFD). Steady-state simulations were performed in ANSYS Fluent employing the standard k–ε turbulence model, with air properties, inlet velocity (9.97 m/s), and thermal boundary conditions defined based on operational data. The results reveal that outlet configuration significantly affects flow recirculation intensity and temperature uniformity across the briquette racks. The four-outlet configuration produced the most homogeneous airflow distribution and reduced thermal gradients, thereby enhancing convective heat transfer effectiveness compared to single- and double-outlet designs. Conversely, the single-outlet case exhibited pronounced recirculation zones and localized temperature variations, potentially leading to uneven drying. These findings demonstrate that optimizing outlet arrangement is a critical design parameter for improving drying efficiency and energy utilization in briquette oven systems, providing a validated numerical framework for future thermal system optimization.